Dialect variation in Indonesian students’ English speech: The role of regional background and language exposure - Suci Pole Mappaita; Muhammad Rifqi Syamsuddin (Researcher and Lecturer Society, 2026)
Dialect variation in English speech among English as a Foreign Language (EFL) learners is often shaped by learners’ linguistic backgrounds and experiences with English exposure. In multilingual contexts such as Indonesia, regional language influence may contribute to variation in pronunciation, intonation, and spoken language performance. This study investigates dialect variation in Indonesian students’ English speech by examining the influence of regional background and language exposure on spoken English performance. Employing a descriptive qualitative approach, this study involved seven university students from South Sulawesi and West Sulawesi, Indonesia, selected through purposive sampling to represent diverse linguistic backgrounds and levels of English exposure. Data were collected through semi-structured interviews and spontaneous speaking tasks and analyzed using thematic qualitative analysis. The findings reveal that students’ English speech varied in pronunciation, intonation, fluency, and confidence in speaking, influenced by multiple interconnected factors. Regional background contributed to pronunciation differences through phonological transfer, while greater exposure to English through academic activities, digital media, peer interaction, and self-directed learning supported stronger fluency and more consistent pronunciation. Educational experiences encouraging active English use also positively influenced spoken performance. In addition, speaking anxiety emerged as a factor affecting learners’ oral communication. The study highlights that variation in students’ English speech should be understood as a reflection of multilingual experiences and linguistic diversity rather than solely as a pronunciation deficiency. These findings contribute to more inclusive English language teaching practices that recognize diverse linguistic backgrounds in EFL learning contexts.